Monitoring phagocytic uptake of amyloid β into glial cell lysosomes in real time. Issue 32 (21st July 2021) - Prakash, Priya; Jethava, Krupal P.; Korte, Nils; Izquierdo, Pablo; Favuzzi, Emilia; Rose, Indigo V. L.; Guttenplan, Kevin A.; Manchanda, Palak; Dutta, Sayan; Rochet, Jean-Christophe; Fishell, Gord; Liddelow, Shane A.; et al.
Abstract : Glial cell phagocytosis of pH-dependent amyloid-β, Aβ pH, in live and fixed cultures, brain tissue sections, retina, cortex and in live animals useful for studying function in health and disease. Abstract : Phagocytosis by glial cells is essential to regulate brain function during health and disease. Therapies for Alzheimer's disease (AD) have primarily focused on targeting antibodies to amyloid β (Aβ) or inhibitng enzymes that make it, and while removal of Aβ by phagocytosis is protective early in AD it remains poorly understood. Impaired phagocytic function of glial cells during later stages of AD likely contributes to worsened disease outcome, but the underlying mechanisms of how this occurs remain unknown. We have developed a human Aβ1–42 analogue (Aβ pH ) that exhibits green fluorescence upon internalization into the acidic organelles of cells but is non-fluorescent at physiological pH. This allowed us to image, for the first time, glial uptake of Aβ pH in real time in live animals. We find that microglia phagocytose more Aβ pH than astrocytes in culture, in brain slices and in vivo . Aβ pH can be used to investigate the phagocytic mechanisms responsible for removing Aβ from the extracellular space, and thus could become a useful tool to study Aβ clearance at different stages of AD.